Kenny music performance anxiety inventory: contribution for the Portuguese validation - Dias, Pedro (2022)
(1) Background: The aim of the present study was to contribute to the validation of the Portuguese version of the Kenny Music Performance Anxiety Inventory (K-MPAI) and to study its psychometric properties. (2) Methods: A sample of 164 undergraduate music students in Portugal (62.2% female; mean age = 22.63; SD = 4.36) completed an online survey composed of the K-MPAI Portuguese version, the State Trait Anxiety Inventory, and a sociodemographic questionnaire. The K-MPAI psychometric properties were examined using exploratory factor analyses, known-group differences, and Cronbach’s alpha. (3) Results: A four-factor structure was identified, in line with recent validation of this measure in other countries: music performance anxiety-related symptoms, depression and hopelessness, parental support, and memory self-efficacy. Concurrent and known group validity were established, and reliability scores were appropriate for the dimensions and total score. (4) Conclusions: The results provide initial evidence of the appropriateness of the Portuguese version of the K-MPAI.